Toxic epidermal necrolysis‐like acute graft‐versus‐host disease in pediatric bone marrow transplant patients: Case series and review of the literature. Issue 6 (21st June 2022) - Sheu Song, Johanna; Huang, Jennifer T.; Fraile Alonso, Maria del Carmen; Antaya, Richard J.; Price, Harper N.; Funk, Tracy; Francois, Rony A.; Shah, Sonal D.
Abstract: Background/Objectives: Complications of hematopoietic stem cell transplant (HSCT) include acute graft‐versus‐host disease (aGVHD). Severe cutaneous aGVHD can present with generalized erythroderma, desquamation, and bullae which can mimic toxic epidermal necrolysis (TEN). TEN occurs in response to a culprit medication. Transplant patients are often on many medications, making it difficult to distinguish between the two conditions. Given that TEN‐like aGVHD is rare, we describe a case series of pediatric patients and review the literature. Methods: This is a multi‐institutional case series of children who developed TEN‐like aGVHD following bone marrow transplantation. Demographic, clinical, and treatment information was collected. Results: Ten patients were identified. Median age at transplantation was 8.5 years (range 0.12–17 years). Median time from transplant to first skin symptoms was 35 days (range 6–110 days) and to first TEN‐like symptoms was 40 days (range 16–116 days). 7/10 had other organ GVHD involvement. All patients were on concurrent medications at time of first skin symptoms including immunosuppression for GVHD prophylaxis, infection prophylaxis or treatment, and pain medication. Treatments for TEN‐like aGVHD included immunosuppression. Conclusions: We observe that patients with > or equal to 50% BSA involvement of their skin with TEN‐like aGVHD, extracutaneous GVHD, and lack of reepithelization tend to have poor outcomes. Given the rarity of this condition, multidisciplinary care of these patients is important for accurate and timely diagnosis and treatment.